2022
DOI: 10.3390/agriculture12101726
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Differentiation and Driving Factors of China’s Agricultural Eco-Efficiency Considering Agricultural Carbon Sinks

Abstract: Climate change, greenhouse gas emissions, and food security have put forward higher requirements for sustainable agricultural development. Agricultural ecological efficiency (AEE) is an important indicator to evaluate the sustainable development of agriculture. Low carbon agriculture promotes sustainable agricultural development. Agricultural carbon sinks are an important output of agricultural production, but they have not been fully reflected in the current research on agricultural ecological efficiency. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The calculation formula is as follows: where, ACS stands for agricultural carbon sinks, i is a specific crop, whereas m is the total number of crop types (here is 11); CAR i denotes the CO 2 absorption rate of crop i, AY i is the yield of crop i, and Q i is the water content of fruit when crop i is ripe; H i represents the economic coefficient of crop i, which is the ratio of economic yield to biological yield. The correlation coefficient of crops involved in the calculation of agricultural carbon sinks is cited from the work by Li et al (2022) [ 38 ], Cui et al (2022) [ 39 ] and Chen et al (2020) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The calculation formula is as follows: where, ACS stands for agricultural carbon sinks, i is a specific crop, whereas m is the total number of crop types (here is 11); CAR i denotes the CO 2 absorption rate of crop i, AY i is the yield of crop i, and Q i is the water content of fruit when crop i is ripe; H i represents the economic coefficient of crop i, which is the ratio of economic yield to biological yield. The correlation coefficient of crops involved in the calculation of agricultural carbon sinks is cited from the work by Li et al (2022) [ 38 ], Cui et al (2022) [ 39 ] and Chen et al (2020) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Li and Zhou [19] explored the role of technology in the effect between the agricultural GDP and agricultural carbon emission, and they found that technology has a positive effect on the reduction of the agricultural carbon emission. Li et al [20] found that the rise in agricultural ecological efficiency will cause sustainable and high-quality agricultural development. Given by the coupling coordination model, Xia et al [21] found that there is a significant positive relation between agricultural carbon emission and agricultural development, and this effect is relatively larger in northern China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, they also adopt deep ploughing and deep loosening technology to improve soil fertility; in the selection of fertilizers, organic fertilizer's long-time effects shall be considered and low pollution shall be selected for as far as possible to reduce the application of chemical fertilizers [34]. Through the use of precise and efficient fertilization technology and the substitution of organic fertilizers, agricultural production trusteeship can effectively reduce the input of chemical fertilizers and reduce the carbon emission generated by the use of chemical fertilizers [35].…”
Section: Effect Of Chemical Fertilizers Reductionmentioning
confidence: 99%